O IMPACTO DA INFLUÊNCIA SOCIAL SOBRE A INTENÇÃO DE USO DE SITES DE COMPRAS COLETIVAS: UM ESTUDO BASEADO NO MODELO UTAUT - Tacco, Fabiana Martins de Souza (2011)
The acceptance and use of Information Technology (IT) by the individual have been studied by different conceptual models that, in general, derived from theories of psychology as the TRA - Theory of Reasoned Action and TPB - Theory of Planned Behavior, derived from the first. An important analysis‟ model derived from it, resulted of thorough analysis of eight other previous models, for while UTAUT - Unified Theory of Acceptance and Use of Technology in VENKATESH et. al. (2003) has been extensively analyzed and validated in many scenarios and technology environments. This work seeks to understand a broader way of background factors on the intended use and usage behavior UTAUT from the model, as well as the factors that best explain the intention and usage behavior, as well as the analysis of moderators. In its development, Venkatesh et al. made comparisons in three deployment stages and in two scenarios: in mandatory adoption, the one that occurred in a business environment where the system is required to process execution and decision making, and voluntary adoption scenario in which the adoption takes place by the individual. In the second case, the authors concluded that "social influence" factor has a low magnitude and significance, not being revealed as an important factor in technology adoption. This study aims to examine too whether the same phenomenon occurs that is given up for voluntarily adoption, but able to be highly influenced by social ties, such as occurs among users of social networks like Orkut, Facebook, Twitter and Linkedin, especially in technologies that enable the financial gains associated with these ties, such as the use of collective purchasing sites such as Peixe Urbano, Clickon and Groupon. Based on the model UTAUT, we applied a research and were later analyzed the results of 292 respondents who were validated accessed through social networks. The technique used consisted of using structural equation modeling, based on PLS - Partial Least Square, with 1000 bootstrap re-sampling. The results demonstrated high predictive significance and magnitude of the Intention of technology use by factors of Expected Desempenho (0,288 @ 0.1%), and Social Influence (0,176@ 0, 1 %),). The first, consistent with previous studies. Since the magnitude and significance of the latter factor resulted in vastly superior to the original study by Venkatesh et al. (2003) ranged between 0.02 to 0.04, not significant, depending on the data are grouped or not (p.465). The main conclusion of this study is that when considering the phenomenon of collective purchasing in an environment of voluntary adoption, therefore, the social factor is highly influential in the intention to use technology, which contrasts strongly with the original study of UTAUT and presents several possibilities for future research and managerial implications.